Acrolein Contributes to the Neuropathic Pain and Neuron Damage after Ischemic–Reperfusion Spinal Cord Injury. (1st August 2018) - Lin, Yazhou; Chen, Zhe; Tang, Jonathan; Cao, Peng; Shi, Riyi
Highlights: Acrolein, a reactive aldehyde, is elevated in spinal cord tissue and urine in rat ischemia–reperfusion spinal cord injury. Phenelzine, a known aldehyde scavenger, reduced acrolein and pain-like behavior, and improved motor neuron survival. Acrolein is likely a key pathological factor in hyperalgesia and motor neuron death in ischemic SCI. Similar to mechanical SCI, anti-acrolein strategy could offer analgesic and neuroprotective effect in ischemic SCI. Abstract: Besides physical insult, spinal cord injury (SCI) can also result from transient ischemia, such as ischemia–reperfusion SCI (I/R SCI) as a postoperative complication. Increasing evidence has suggested that oxidative stress and related reactive aldehyde species are key contributors to cellular injury after SCI. Previous work in spinal cord contusion injury has demonstrated that acrolein, both a key product and an instigator of oxidative stress, contributes to post-traumatic hyperalgesia. It has been shown that acrolein is involved in post-SCI hyperalgesia through elevated activation, upregulating, and sensitizing transient receptor potential ankyrin 1 (TRPA1) in sensory neurons in dorsal root ganglia. In the current study, we have provided evidence that acrolein likely plays a similar role in hypersensitivity following I/R SCI. Specifically, we have documented a post-I/R SCI hypersensitivity, with parallel elevation of acrolein locally (spinal cord tissue) and systemically (urine), which was also accompanied by augmented TRPA1 mRNA in DRGs. Interestingly, known aldehyde scavenger phenelzine can significantly alleviate post-I/R SCI hypersensitivity, reduce acrolein, suppress TPRA1 upregulation, and improve motor neuron survival. Taken together, these results support the causal role of acrolein in inducing hyperalgesia after I/R SCI via activation and upregulation of TRPA1 channels. Furthermore, endogenously produced acrolein resulting from metabolic abnormality in the absence of mechanical insults appears to be capable of heightening pain sensitivity after SCI. Our data also further supports the notion of acrolein scavenging as an effective analgesic as well neuroprotective strategy in conditions where oxidative stress and aldehyde toxicity is implicated.